2021
DOI: 10.1542/peds.2020-032490
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in South African Children and Adolescents Routinely Treated for Tuberculosis

Abstract: BACKGROUND: In South Africa, tuberculosis (TB) is a leading cause of death among those <20 years of age. We describe changes in TB mortality among children and adolescents in South Africa over a 13-year period, identify risk factors for mortality, and estimate excess TB-related mortality. METHODS: Retrospective analysis of all patients <20 years of age routinely recorded in the national electronic drug-susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…In most published reports, ≥80% of AYAs are treated successfully for drug-susceptible TB. Most adolescents with unfavorable outcomes are lost to follow-up; <5% die [10,45]. An analysis of drug-susceptible TB treatment outcomes between 2004 and 2016 in South Africa demonstrated age-disaggregated case-fatality (CFRs) between 2.3 and 4.3 for adolescents; notably, the CFR peaked for boys in mid-adolescence and for girls in late adolescence [45].…”
Section: Tb Treatment Outcomes and Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…In most published reports, ≥80% of AYAs are treated successfully for drug-susceptible TB. Most adolescents with unfavorable outcomes are lost to follow-up; <5% die [10,45]. An analysis of drug-susceptible TB treatment outcomes between 2004 and 2016 in South Africa demonstrated age-disaggregated case-fatality (CFRs) between 2.3 and 4.3 for adolescents; notably, the CFR peaked for boys in mid-adolescence and for girls in late adolescence [45].…”
Section: Tb Treatment Outcomes and Adherencementioning
confidence: 99%
“…Most adolescents with unfavorable outcomes are lost to follow-up; <5% die [10,45]. An analysis of drug-susceptible TB treatment outcomes between 2004 and 2016 in South Africa demonstrated age-disaggregated case-fatality (CFRs) between 2.3 and 4.3 for adolescents; notably, the CFR peaked for boys in mid-adolescence and for girls in late adolescence [45]. In the same South African cohort, children and adolescents (0-19 years old) with HIV and TB had a CFR of 4.8 if they were receiving ART and 6.3 if they were not on ART; in comparison, children and adolescents without HIV had a CFR of 1.0 from TB [45].…”
Section: Tb Treatment Outcomes and Adherencementioning
confidence: 99%
“…Increased TB risk for females relative to males appears to peak at mid-adolescence [2,10]. Sex differences are also seen in TB-related mortality, which may intersect with higher vulnerability to HIV among female AYA [2,10,12]. A study in Cape Town, South Africa, a region with high TB and HIV prevalence, found that of adolescents aged 15-19 years with drug-susceptible TB, female adolescents had more than twice the risk of mortality than male adolescents [12].…”
Section: Prevalence Gender and Risk Factors For Aya Tbmentioning
confidence: 99%
“…Among young adults and older individuals, the higher TB risk shifts to males [2,10]. Reasons for these shifting sex differences remain unclear but may reflect a combination of factors [2,10,12]. Proposed influences include factors increasing susceptibility to TB among female adolescents (due to physiologic changes at menarche, a higher incidence of HIV infection among female AYA, TB risks associated with pregnancy, and/or other drivers yet to be identified) or factors resulting in undiagnosed TB among male adolescents, who might be less likely to access care to receive a TB diagnosis and/or may face higher mortality from interpersonal violence or other noninfectious causes [2,10,12].…”
Section: Prevalence Gender and Risk Factors For Aya Tbmentioning
confidence: 99%
See 1 more Smart Citation